2016
DOI: 10.1158/1078-0432.ccr-15-0715
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 and HLA Class I Antigen Expression and Clinical Course of the Disease in Intrahepatic Cholangiocarcinoma

Abstract: Purpose More effective therapy is needed for intrahepatic cholangiocarcinoma (ICC). The encouraging clinical results obtained with checkpoint molecule-specific monoclonal antibodies (mAb) have prompted us to investigate whether this type of immunotherapy may be applicable to ICC. The aims of this study were to determine whether (i) patients mount a T-cell immune response to their ICC, (ii) checkpoint molecules are expressed on both T cells and tumor cells, and (iii) tumor cells are susceptible to recognition b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
168
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(187 citation statements)
references
References 38 publications
15
168
2
2
Order By: Relevance
“…In addition, the expression in tumour cells of the specific uptake transporter for bile acids, the apical sodium-dependent bile acid transporter (ASBT), has suggested the possibility of using cytostatic bile acid derivatives, such as the ursodeoxycholic acid-cisplatin conjugate BAMET-UD2, in targeted chemotherapy for CCA 270 . In 2015, the rationale for immunotherapy with checkpoint-molecule-specific monoclonal antibodies in patients bearing iCCA without defects in HLA class I antigen expression has been provided 271 but, so far, no clinical trial has been performed. Crucially, it must be underscored that the management of CCAs should only be undertaken in dedicated tertiary units with access to multidisciplinary approaches.…”
Section: Biliary Stentingmentioning
confidence: 99%
“…In addition, the expression in tumour cells of the specific uptake transporter for bile acids, the apical sodium-dependent bile acid transporter (ASBT), has suggested the possibility of using cytostatic bile acid derivatives, such as the ursodeoxycholic acid-cisplatin conjugate BAMET-UD2, in targeted chemotherapy for CCA 270 . In 2015, the rationale for immunotherapy with checkpoint-molecule-specific monoclonal antibodies in patients bearing iCCA without defects in HLA class I antigen expression has been provided 271 but, so far, no clinical trial has been performed. Crucially, it must be underscored that the management of CCAs should only be undertaken in dedicated tertiary units with access to multidisciplinary approaches.…”
Section: Biliary Stentingmentioning
confidence: 99%
“…Upregulation of PD-1/PD-L1 was demonstrated in a different set of intrahepatic CCA [58]. Dysregulation of immune checkpoint molecules was associated with less differentiated histology, more advanced tumor stage and worse outcome while HLA 1 overexpression seems to have inverse effect [59]. There is very few data on clinical use of immune therapeutics in CCA.…”
Section: Immunotherapy In Ccamentioning
confidence: 99%
“…Here, the median PFS was 156 days and the OS 380 days. It was also shown that programmed cell death ligand 1 (PD-L1) and human leukocyte antigen (HLA) class I is expressed in human intrahepatic CC [59]. The authors confirmed that positive HLA class I expression in combination with negative/low PD-L1 expression was associated with better clinical disease and that their findings support the usage of immunotherapeutic checkpoint inhibitors.…”
Section: New Targets and Therapiesmentioning
confidence: 90%